KOMPOSISI BOTANI DAN PERSEBARAN JENIS-JENIS HIJAUAN PADA PADANG PENGGEMBALAAN ALAM DI KECAMATAN TELUK AMBON, KOTA AMBON - Nunumete, Indry; Fredrikzs, Shirley; Patty, Christian Willem (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to describe the botanical composition of natural pastures in Teluk Ambon District, Ambon City, and identify the dominant plants. Conducted in Laha and Tawiri Villages for one month, data were collected through quadrant sampling and dry weight rank analysis. The results showed that pastures were dominated by grasses (Poaceae), with the highest proportion in Laha Village (85.22%). Legumes were <10%, while non-feed species were higher in Tawiri Village (20%). Dominant plants were: Axonopus compressus, Cynodon dactylon, Digitaria sanguinalis, and Grona triflora. This indicates that natural pastures in Teluk Ambon District are dominated by grasses (Poaceae). Laha Village has better forage quality than Tawiri Village due to the higher proportion of productive grasses and legumes. These findings provide an important basis for sustainable forage improvement and management in the region. It is recommended to regulate the time livestock enter pastures to ensure grass availability, add legumes or nutritious forages to improve feed quality, and control non-forage plants to maintain optimal forage productivity.